KEJAHATAN MONEY LOUNDERING DI TINJAU DARI SEGI SOSIOLOGI HUKUM - Nyimas Enny Fitriya Wardhany (Jurnal LEX SPECIALIS, 2012)
AbstractMoney loundreing is a process that uses the money from the criminal acts hidden or obscured by origin by the perpetrator, so that later appeared as if the money is legitimate or lawful money, this paper answers about the crimes committed by offenders who fail to comply with the law and the factor-factors that influence it through the sociology of law. Key Note : Crime, Prevention and Eradication